GE_GERICHTE P/9079/2024 vom 22. Dezember 2025 - GE Cour de justice (2025)
DÉFAUT(CONTUMACE);VIOL;CONTRAINTE SEXUELLE;LÉSION CORPORELLE SIMPLE;VOL(DROIT PÉNAL);TENTATIVE(DROIT PÉNAL);LÉGITIME DÉFENSE;EXPULSION(DROIT PÉNAL);PARTIE CIVILE | CP.190; CP.189; CPP.405; CPP.407; CP.123; CP.139; CP.22; CP.15; CP.66a; CPP.120; CPP.122